Liberia : Gender-Aware Programs and Women's Roles in Agricultural Value Chains - World Bank (Washington, DC, 2014)
This Policy Memorandum provides policy advice to the government of Liberia (GOL) in an effort to mainstream gender issues in policies, programs, and projects supporting agricultural production and value-chain development. It is organized as follows. Section I reviews women's roles in Liberian agriculture and agricultural value chains, drawing on a variety of data sources, including the 2007 Core Welfare Indicator Questionnaire Survey (CWIQ) and the two rounds of the Comprehensive Food Security and Nutrition Survey (CFSNS, 2006 and 2008). It also gives an overview of the agricultural sector in Liberia. Section II uses the same sources to analyze key constraints faced by women as agricultural producers and in value-adding activities, as well as key crop-specific issues in cassava, rice, and tree crops. Section III reviews the engagement of the GOL in gender-aware agriculture programs and recommends some key general principles to support gender-aware interventions, and specific recommendations aimed at supporting women as agricultural producers and increasing access to, and better efficiency in, value addition. Section IV discusses the institutional issues that need to be considered to support the design, implementation and monitoring of interventions. Finally, Section V discusses the availability and the role of appropriate gender aware data as the basis for policy programming and monitoring of interventions.